Peran Pesantren Mahasiswa sebagai Katalisator Transformasi Akhlak - Adam Mubarak; An Naafi’ Khoyrunnisaa; Nadine Aulin Naysilla; Raffindra Farouq Al Barru; Sabrina Aufa Fadhilah; Sidiq Rahmadi (LaKaspia, 2025)
University students are widely regarded as agents of future social transformation, and the consequences of their actions inevitably reverberate within society. In recent years, however, increasing instances of students exhibiting unethical behavior and deviating from established social norms have raised serious concerns. Misguided social interactions and unfavorable environments have been identified as contributing factors to this moral decline. This study examines the role of student pesantren as catalysts for moral transformation among university students. The research aims to analyze how student pesantren function as formative spaces capable of fostering positive changes in the character of students at UIN Raden Mas Said Surakarta. Adopting a qualitative research design, the study employs interview techniques within a case study approach. Data were collected through in-depth interviews with three purposively selected students residing in a student pesantren. The findings indicate that the pesantren environment contributes significantly to students’ moral development. The regulatory framework, disciplinary practices, and structured religious learning embedded within the pesantren cultivate disciplined and ethically sound behavior. Moreover, the social and spiritual atmosphere of the pesantren provides an enabling environment that reinforces moral refinement. Consequently, student pesantren emerge as a viable alternative for nurturing and strengthening commendable character among university students.